The Effects of Environmental Problem-based Learning Method on Malaysian Primary ESL Learners’ Vocabulary Achievement - Zachary Farouk Chai; Suyansah Bin Swanto (Institut Agama Islam Negeri Palopo, 2020)
Environmental education has long been introduced as early as the 18th century in western countries, but in Malaysia, it still can be considered as a new start in the year 1979. In relation to this, various programs have been conducted by the government to produce literate individuals that are aware of and concern of environmental issues. In primary English education, there are a few topics on the environment that should be taught by teachers, and environmental education is also considered as a cross-curricular subject. The present study aimed to investigate the effects of environmental problem-based learning (PBL) on Malaysian primary school learners' vocabulary achievement. Environmental PBL is an instructional method that provides learners the opportunities to learn cooperatively in groups to find solutions to any problem. This study employed experimental design, which involved 20 learners that came from an intermediate level of English proficiency. They were randomly divided into experimental group and control group. The experimental group was treated with environmental PBL in learning new vocabulary, while the other group was taught using the conventional memorisation method. A set of vocabulary test (pre and post) was used to measure learners' vocabulary achievement and the data were analysed by using independent sample t-test. From the data, it was found out that the learners who were taught by using environmental PBL improved their vocabulary acquisition significantly as being compared to the control group based on the means of marks obtained by the research participants in the experimental group with 12.80 and the mean achieved by the control group with 6.20. Next, this study also showed how environmental PBL helped the experimental group in learning vocabulary based on their orientations which included two themes (effectiveness and participation). Hence, it is suggested that English teachers should use environmental PBL as an effective method of teaching vocabulary to young learners.